The Effect of Total Quality Management on Service Quality, Price, and Customer Satisfaction at Kita-Kita Tour and Travel - Nugraha, Isna; Ramadhan, Gilang (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2024)
This study aims to analyze the effect of Total Quality Management (TQM) implementation on service quality and price and its impact on customer satisfaction at Kita-Kita Tour and Travel. This study uses a quantitative method with a casual associative approach to measure service quality variables (X1), price (X2), and customer satisfaction (Y). Data was collected through questionnaires distributed to consumers who have used Kita-Kita Tour and Travel services, and was analyzed using SPSS software. Data that meets the validity, reliability, and classical assumption tests are then processed to produce a linear regression equation. The results of the analysis show that service quality and price partially and simultaneously have a positive and significant effect on customer satisfaction, so the hypothesis is accepted. The reliability test resulted in a Cronbach's Alpha value of 0.864, indicating that the data obtained is reliable. Based on this research, it shows that the implementation of TQM has a positive impact on service quality and price, which in turn increases customer satisfaction.